ACTIVE CONSTITUENTS AND BIOLOGICAL ACTIVITY OF METHANOLIC EXTRACT OF FORSSKAOLEA VIRIDIS AERIAL PARTS: PHENOLIC CONSTITUENTS AND THEIR BIOLOGICAL ACTIVITY OF METHANOLIC EXTRACT OF FORSSKAOLEA VIRIDIS AERIAL PARTS - ALY AHMED, FATMA; EL-BASSOSSY, TAHA A. I. (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study is to isolate and evaluate the antioxidant, antimicrobial, and antitumor activity of the methanolic constituents of Forsskaolea viridis. Methods: The isolation and purification of phytochemical constituents were performed in the present study using various chromatographic methods (thin-layer [TLC], preparative paper [PPC], and column chromatography [CC]) where, the structures of isolated compounds were determined using different spectroscopic methods (Mass spectroscopy [Ms], ultraviolet [UV], proton and carbon nuclear magnetic resonance [1H-NMR and 13C-NMR]) and confirmed by data reported in the literature. The biological activity of the methanolic extract was performed as in vitro studies by diffusion agar technique, 2,2-Diphenyl-1-picrylhydrazyl hydrate (DPPH), and 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay for antimicrobial, antioxidant, and antitumor activity, respectively. Results: The chemical studies led to the isolation of five flavonoids and two phenolic compounds for the first time from this plant. The methanolic extract exhibited potent antimicrobial activity (13–26 mm) against some of the tested strains while it showed fair antioxidant and cytotoxicity activity. Conclusion: It can be concluded from the results that the methanolic extract of F. viridis has potential antimicrobial activity while fair antioxidant and antitumor activity.